Dynamic Interactions in Macroeconomic Activities - Lee Chee Loong; Laiu Chun Hao; Ramli Nur Hidayah; Mohd Palel Nur Sabrina (Pertanika Journal of Social Sciences and Humanities, 2018)
This paper empirically investigates the dynamic interaction of macroeconomic activities for the ASEAN 5 (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) with consideration of the asymmetric adjustment in this interaction. Both the short and long-run interactions were modelled during 1960-2014, and there were differences for each country based on data availability. The empirical results of the analysis were based on time series data and are summarized as follows: i) Indonesia and the Philippines had no evidence for cointegration; ii) among those countries, it was found that only Malaysia has asymmetric adjustment regarding cointegration; iii) money supply responded only to positive shocks while the interest rate responded only to negative shocks; iv) only unidirectional causal relationship was found in the long-run and short-run methods. Based on the results, the wisest operating target for Indonesia and Thailand is inflation targeting. Monetary aggregate targeting would be the recommended operating policy for the Philippines and Singapore. Malaysia should implement exchange rate targeting and intervene in the money supply (when there is a negative shock) and in the interest rates (when there is a positive shock).
Keywords: E52; 330; ASEAN 5; Asymmetric adjustment; intermediate targeting; operating targeting